Selected Topics on Business Informatics: Editorial Introduction to Issue 19 of CSIMQ - Sandkuhl, Kurt; Zdravkovic, Jelena (Complex Systems Informatics and Modeling Quarterly, 2019)
The objective of this thematic issue was twofold. The first it was to present selected research results of the 17th International Conference on Perspectives in Business Informatics Research (BIR2018) in Stockholm, Sweden, in September 24–26, 2018. The conference created a productive forum for researchers and practitioners on the specific topic – Business Resilience, with the intention of exploring organizational and information system resilience in congruence. Top papers were selected by the Program Chairs Prof. Janis Grabis and Prof. Jelena Zdravkovic to submit extended versions for a possible publication to this thematic issue. The second objective was to consider external candidate submissions for bringing attention to recent research in the Business Informatics discipline and thus make this issue even more actual. Five articles were selected that report on research in ecosystem architecture management, strategic coopetition, deriving enterprise architecture model from data, hierarchic viewpoints in control compliance assessments, and operationalizing enterprise IT architecture.